Querida Mia - Arauz, Carlos (Revista Universidad de Guayaquil, 1998)
I love you, vanitywith the shynessof a provincial priestalmost forced to hidebehind the statues I love you, my vanitywith the cowardiceof light curtainsthat only hintsallow to glimpse I love you, vanityfor the flag of pridesecret charm of the heart